Modlin Fortress as a Military Garden of the Second Republic - Zbigniew Kazimierz Mikołajczyk (The Francis de Sales Scientific Society (TNFS.PL), 2021)
The interwar period was a time of rapid development of our statehood. After 123 years, Poland regained its independence and began the reconstruction of the devastated country. The main task was to ensure the security of the state by creating a strong army. The Modlin Fortress, due to its convenient location and the existing infrastructure, was a suitable place to set up a strong garrison. Many military units were brought there to create training centres for various types of armed forces. Housing estates were developed to accommodate soldiers and their families. This large garrison quickly became a significant centre of military, educational, cultural, and religious life.